Initial Public Offering as a Means of Raising Capital - the Advantages and Disadvantages of the Initial Public Offering - Michorowski, Michał (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
The key decisions made by a managing director should always be based on the analysis of the enterprise’s requirements and financial possibilities. Without this knowledge, some investments could face the serious risk of failure. Many forms of raising capital allow investment aims to be tailored so as to be adequately implemented. Moreover, the selected method should coincide with the company’s economic situation. Thanks to today’s constant development of the capital markets and global free cash flow, the stock exchange has become one of the best alternative ways of raising capital. The paper presents the numerous positive and negative aspects of the IPO with consideration of the cost of raising capital and corporate policy. It is based on data on IPOs from the Warsaw Stock Exchange in the years 2005-2010.